0584 Impact of Obstructive Sleep Apnea on Chronic obstructive pulmonary disease Hospitalizations. (25th May 2022) - Al Khateeb, Mohannad; Yusuf, Mubarak; Horoub, Ali; aldiabat, Mohammad; Jabiri, Yazan Al
Abstract: Introduction: Obstructive sleep apnea (OSA) is a sleep disorder that has been linked to increase the risk for hypertension, ischemic heart failure, arrhythmia and heart failure. There are multiple similarities between OSA and Chronic Obstructive Pulmonary Disease (COPD); both are associated with hypoxia and hypercapnia, with different mechanisms of hypoxia; in COPD its chronic and slow progression, whereas it is suddenly intermittent hypoxia in OSA. Intermittent hypoxia was hypothesized to enhance the protective effect on subsequent hypoxia resulting in cardioprotective effect [1]. There is little data on rates of in-hospital mortality on patients with OSA and COPD using a nationwide study. In this study, we aim to analyze the impact on mortality and length of hospital stay of obstructive sleep apnea in patients with COPD. Methods: Adults with principal diagnosis of COPD were selected from the 2019 US National Inpatient Sample, using ICD 10 code primary diagnosis on discharge. We queried the 2019 National Inpatient Sample for OSA, and other secondary diagnoses (hyperlipidemia, hypertension, heart failure, smoking, CKD, electrolytes disturbances). Confounders were adjusted for using multivariable linear regression analysis for other secondary diagnoses. Results: In a total of 520, 624 adult hospitalizations with COPD primary diagnosis on discharge were included from the 2019 national inpatient sample. 73, 705 patients had concomitant secondary diagnosis with OSA. On weighted analysis, hospitalizations with primary diagnosis of COPD and secondary diagnosis of OSA had lower in-hospital mortality rates compared to hospitalizations with COPD alone (0.6% vs 1.08%, p= 0.000), .COPD hospitalizations with OSA had statistically significant lower odds for mortality compared to COPD patients without OSA (adjusted OR 0.73, 95% CI 0.57-0.93; p= 0.009).However, COPD hospitalizations with OSA showed increased in the mean length of stay by 0.21 days (95% CI 0.12-0.30, p=0.000) compared to patients without OSA. Conclusion: Our analysis showed better mortality outcomes for COPD patients with OSA, supporting the protective effect hypothesis of intermittent hypoxia. COPD patients with concomitant secondary OSA diagnosis have increased in-hospital length of stay. Support (If Any): 1- Murry CE, Jennings RB, Reimer KA (1986) Preconditioning with ischemia: a delay of lethal cell injury in ischemic myocardium. Circulation 74:1124–1136